2019
DOI: 10.1111/lang.12333
|View full text |Cite
|
Sign up to set email alerts
|

Domain‐General Cognitive Ability Predicts Bilingual Children's Receptive Vocabulary in the Majority Language

Abstract: This study investigated the influence of cognitive ability on bilingual children's vocabulary development in both their languages. Sixty‐nine bilingual immigrant children participated, with data collected at three annual intervals. At Time 1, the participants were 5 or 6 years old. Receptive vocabulary was tested in the minority (Turkish, Tarifit) and majority (Dutch) languages. Cognitive measures targeted working memory, selective attention, and executive attention. Cross‐lagged correlations were computed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…This could be due to a task-effect of reported behavior, as Dutch families with migration backgrounds are commonly subjected to discrimination and marginalization (Van de Weerd, 2019) and experience societal and political pressure to learn Dutch which, in turn, may lead to overreporting their use of Dutch. However, another study, based on the same sample, revealed that the parents’ report of amount and richness of Turkish and Tarifit at home correlates significantly with the Turkish–Dutch and Moroccan–Dutch children’s vocabulary scores in Turkish and Tarifit respectively (Blom, 2019), confirming the reliability of parental report of language use at home. The migrant languages of the Distant group may, in general, be less widely used outside the home environment than the regional languages in the Close group since these regional languages are also community languages.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This could be due to a task-effect of reported behavior, as Dutch families with migration backgrounds are commonly subjected to discrimination and marginalization (Van de Weerd, 2019) and experience societal and political pressure to learn Dutch which, in turn, may lead to overreporting their use of Dutch. However, another study, based on the same sample, revealed that the parents’ report of amount and richness of Turkish and Tarifit at home correlates significantly with the Turkish–Dutch and Moroccan–Dutch children’s vocabulary scores in Turkish and Tarifit respectively (Blom, 2019), confirming the reliability of parental report of language use at home. The migrant languages of the Distant group may, in general, be less widely used outside the home environment than the regional languages in the Close group since these regional languages are also community languages.…”
Section: Discussionmentioning
confidence: 69%
“…The results showed that bilingualism predicted a significant amount of variance in Dutch receptive vocabulary scores over and above the effects of nonverbal intelligence and socioeconomic status, measured through the parents’ level of education: the full bilingual group, not differentiated by language pair, scored on average lower on Dutch receptive vocabulary than monolingual Dutch controls. Children with more mental resources, who obtained higher nonverbal intelligence scores, knew more Dutch words, indicating that vocabulary development is driven by domain-general cognitive processes (Blom, 2019; Paradis, 2011). In addition, children whose parents were more highly educated had larger vocabularies.…”
Section: Discussionmentioning
confidence: 98%
“…These explanations are entirely speculation. However, there are at least two other findings that nonverbal intelligence is related to majority language skills, but not minority language skills in bilingual children (Blom, 2019; Hakuta, 1987), suggesting the relation may be real. If so, this finding raises interesting questions for future research regarding differences among social contexts in the cognitive demands they make of children with respect to language learning.…”
Section: Discussionmentioning
confidence: 97%
“…These standardized scores were used for the matching of bilingual and monolingual children. For the bilingual children, we also administered a Turkish version, which was a translation of the Dutch task for which permission was obtained from the publisher (Blom, 2019). The translation of the task was done by a bilingual speaker of Turkish and Dutch.…”
Section: Language Proficiencymentioning
confidence: 99%